Histometric studies on cellular infiltrates of tuberculin tests in patients with sarcoidosis. - Lowe, J G (1991)
The density and microanatomical location of CD4 and CD8 lymphocytes and of monocytes/macrophages at the site of a tuberculin test were measured in 13 patients with sarcoidosis, and the results were compared with those seen in a group of healthy controls. The cellular infiltrate was significantly reduced in the sarcoid subjects compared with the controls for all cell phenotypes studied; the ratio of CD4 positive:CD8 positive lymphocytes was significantly increased in the sarcoid group. Clinically negative reactions showed substantial numbers of infiltrating mononuclear cells, although not as great as in clinically apparent reactions. A clinically negative tuberculin reaction does not necessarily imply anergy to the test substance and should not be termed "negative".